1982
DOI: 10.3109/10408368209107030
|View full text |Cite
|
Sign up to set email alerts
|

Creatine Kinase

Abstract: Creatine kinase is present in significant concentrations in skeletal muscle and cardiac muscle and to a lesser extent in gastrointestinal tract and brain tissue. The enzyme has been purified from a variety of tissues and an examination of its kinetic and physical properties reveal that the enzyme consists of two subunits and can exist as three isoenzymes containing essential cysteine residues. These properties are important in understanding its stability, the assay conditions, and the techniques used to identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
1

Year Published

1984
1984
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 296 publications
0
33
0
1
Order By: Relevance
“…Therefore, it can be said that LIH index of Olympus can be used to identify the inappropriate hemolyzed samples but this is not reliable enough for CK-MB activity in the samples with normal range. It has been previously documented that adenylate kinase catalyzes the reaction; 2 ADP ßà AMP + ATP, and increased AK levels in hemolyzed samples leads to an apparent increase in creatine kinase activity [14,15]. It can be diminished by the addition of either AMP, which is a weak competitive inhibitor of AK, or diadenosine pentaphosphate, which is a powerful competitive inhibitor (2).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it can be said that LIH index of Olympus can be used to identify the inappropriate hemolyzed samples but this is not reliable enough for CK-MB activity in the samples with normal range. It has been previously documented that adenylate kinase catalyzes the reaction; 2 ADP ßà AMP + ATP, and increased AK levels in hemolyzed samples leads to an apparent increase in creatine kinase activity [14,15]. It can be diminished by the addition of either AMP, which is a weak competitive inhibitor of AK, or diadenosine pentaphosphate, which is a powerful competitive inhibitor (2).…”
Section: Discussionmentioning
confidence: 99%
“…Normal human serum contains MM-CK almost exclusively and it has been suggested that serum BB-CK could be used as a tumour marker (Foreback and Chu, 1981;Bais and Edwards, 1982;Grifflths, 1982;Nanji, 1983;Kanemitsu and Okigaki, 1988). Serum BB-CK increases in patients with small-cell lung carcinoma, which has higher BB-CK levels than the normal lung tissue.…”
Section: Distribution Of Ck Isoenzymes In Liver Normal Tissue and Tummentioning
confidence: 99%
“…Many reports have been published on the distribution of CK subunits and isoenzymes in tumours (for review see Foreback and Chu, 1981;Bais and Edwards, 1982;Griffiths, 1982;Nanji, 1983;Kanemitsu and Okigaki, 1988). However, most data have been obtained by immunohistochemical and immunoassay techniques.…”
mentioning
confidence: 99%
“…Application of the lower creatine kinase-MB fraction limit, with a view to eliminating false positive results arising from either incomplete inhibition of creatine kinase-MM activity (5) or creatine kinase-MB activity from skeletal muscle damage (1,4), has been discussed by others (10,23). The disadvantage is that an acute myocardial infarction could be masked by a simultaneous major release of creatine kinase-MM from non-myocardial sources.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of this specific diagnostic test. The most widely used single study is to compare two different immunoinhibition laboratory test is electrophoretic determination of the methods (a dry and a wet chemistry method) with the MB isoenzyme of creatine kinase (EC 2.7.3.2) 1 ) (crea-commonly used but laborious electrophoretic method, tine kinase-MB) (1,2). This method is very specific and reasonably sensitive, but it is rather tedious and expensive (3,4).…”
Section: Introductionmentioning
confidence: 99%